Young people's perspectives on open communication between family members when a parent is dying - Turner, Nicola (Cambridge University Press, 2017)
Objective: Living with a parent who is approaching the end of life is profoundly troubling for young people. Research indicates that family communication about life-limiting parental illness can influence how young people manage living with dying. In particular, open communication between family members has been shown to be helpful. This paper reports on a study of young people’s experiences of family interaction when a parent is dying and considers the practice of open communication in the context of young people’s involvement in giving and receiving family care.